DYNAMICS OF FOREST FIRES IN THE REPUBLIC OF BURYATIA - A. V. Ignateva; N. V. Baranovskiy (Вопросы лесной науки, 2022)
The Republic of Buryatia is annually exposed to forest fires, resulting in significant damage to the economy, population and ecology of the region. The purpose of this study is to analyze and assess the fire hazard situation on the territory of the Republic of Buryatia from 2013 to 2019. The article presents an analysis of the affected and deceased population of the republic as a result of the impact of the damaging factors of fires. The article analyzes the fire hazard situation in the forestries of Buryatia based on the calculated values of the vulnerability of the territory to fires. According to the analysis of the vulnerability of forest areas, the greatest vulnerability is characteristic of forest areas with a higher population density and a predominance of pine forests in the species composition. Pine is highly combustible and, accordingly, contributes to the rapid spread of fires. The dynamics of the occurrence and spread of fires on the territory of the subject for the period from 2013 to 2019 is also analyzed. Most of the fires that are recorded in the Republic of Buryatia are anthropogenic in nature. Also in 2015, the largest areas of fires, the number of injured and dead people were noted on the territory of the republic.